Examining the effects of mood on quality and feasibility of design outcomes. Issue 2 (3rd April 2021) - Paige, Myela A.; Fillingim, Kenton B.; Murphy, Alexander R.; Song, Hyeonik; Reichling, Catherine J.; Fu, Katherine
ABSTRACT: This study examines the correlation between quality and feasibility of generated design solutions with mood and rational vs. intuitive thinking. It was hypothesized that positive moods lead to better intuitive thinking, which will result in higher design quality and feasibility. The participants, who were junior and senior level undergraduate students with a design background, were given the 32-point Brunel Mood Scale (BRUMS) before solving nine 7-min design tasks in a manner that cultivated either analytical or intuitive thinking. Cronbach's alpha was used to confirm the reliability and consistency of the self-reported mood data. Spearman's correlation was used to illustrate the mood–performance relationship, revealing that high design solution quality is significantly positively correlated with vigor and energetic mood in the Creative Intuition (CI) condition, and downhearted mood in the Problem Solving Intuition condition, while significantly negatively correlated with depression, worn-out and bad-tempered moods in the CI condition. High design solution feasibility was positively correlated with an exhausted mood in the Rational Thinking condition, and negatively correlated with composed and relaxed moods in the CI condition. These findings help further the understanding of how mood impacts design outcomes in intuitive and analytical problem solving, which may have implications design practice.